Iron Content Value in Potato Peel Extract - Ifa Nurhasanah (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Potato peel is a food ingredient that is cheap and easy to obtain. This ingredient can help people fulfill their iron needs so that the production of hemoglobin levels in the blood is not lacking. Potato peel can also be considered as a remedy to prevent and overcome cases of anemia, especially in adolescent girls and pregnant women, who are considered vulnerable groups. Objective: The purpose of this study is to determine the iron content value in potato peel extract. Methods: The research method used a laboratory approach, tested through qualitative and quantitative analysis. The place and time of the research were the Undergraduate Pharmacy Laboratory, Faculty of Health Sciences, Ibrahimy University, from March to July 2024, using a UV-Vis spectrophotometer and potato peel extract samples. Result: The results obtained showed the presence of iron in the research sample, with an iron content value of 11.526 mg in 100 grams. Conclusions: The conclusion of this study is that potato peel extract can be used by processing it into food products that can be consumed daily as needed, in order to avoid anemia.